The Influence of Digitalization of the Tax System, Social Media, and Hedonism Culture on Tax Compliance - Rahmaniasari Tri Utami; Heru Tjaraka; Alfa Rahmiati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of digitalization of the tax system, use of social media, and hedonism culture on tax compliance of Generation Z in Indonesia. Generation Z, born between 1996 and 2013, is a generation that grew up with technology and has unique characteristics. A quantitative approach was used by distributing questionnaires to 160 individual taxpayers of Generation Z who have NPWP. Multiple linear regression analysis with IBM SPSS 25 was used to analyze the data. The results showed that digitalization of the tax system positively impacts tax compliance. Ease of access and transparency encourage taxpayers to be more compliant. The use of social media also contributes to increasing tax compliance. Social media is a means of tax information and education, creating awareness about the importance of paying taxes. However, the hedonism culture inherent in Generation Z can be a barrier. The tendency to prioritize pleasure can reduce the motivation to pay taxes.